2017
DOI: 10.1007/s11060-017-2476-y
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetically controlled Six3 expression regulates glioblastoma cell proliferation and invasion alongside modulating the activation levels of WNT pathway members

Abstract: Glioma is the most common primary brain tumor in adults. Six3 is a human homologue of the highly conserved sine oculis gene family and essential transcription regulatory factor in process of eye and fetal forebrain development. However, little is known about the role of Six3 in human tumorigenesis. The aim of this study is to investigate the methylation/expression of Six3 and reveal its function and action mechanism in glioma. Our results showed that Six3 was down-regulated in human glioma tissues and human gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Moreover, high expression of SIX3 was associated with improved overall and progression‐free survival of patients with lung adenocarcinoma . A similar finding was also observed in patients with glioblastoma . A meta‐analysis suggests that SIX3 may play a role in suppressing the progression of lung cancer, especially in its early stage …”
Section: Discussionsupporting
confidence: 60%
“…Moreover, high expression of SIX3 was associated with improved overall and progression‐free survival of patients with lung adenocarcinoma . A similar finding was also observed in patients with glioblastoma . A meta‐analysis suggests that SIX3 may play a role in suppressing the progression of lung cancer, especially in its early stage …”
Section: Discussionsupporting
confidence: 60%
“…Likewisely, loss of Six3 is involved in the initiation and progression of human glioma via increasing Wnt/β-catenin signaling (B. Zhang, Shen, Ge, Ma, & Zhang, 2017). However, dapper homolog 2 (DACT2) acts as a tumor suppressor to suppress growth and induce apoptosis of glioma cells by inducing Wnt/β-catenin pathway (Y.…”
Section: Suppressive Roles Of Wnt/ β-Catenin Pathway In Glioma Devementioning
confidence: 99%
“…β-catenin, known as a core component of this signaling, has been determined to be a pivotal contributing factor in a wide range of cancers, including GBM; besides, silencing of β-catenin decreased the expression of c-Myc and Cyclin D1 in GBM cells ( Liu et al., 2011 ). It has been documented that Cyclin D1 and c-Myc were involved in regulation of proliferation in GBM ( Cobanoglu et al., 2016 ; Zhang et al., 2017 ). Consistent with this, indeed, we found that nuclear β-catenin, c-Myc, and Cyclin D1 were inhibited by depletion of CLEC18B.…”
Section: Discussionmentioning
confidence: 99%